Informing risky migration: Evidence from a field experiment in Guinea - Giacomo Battiston; Lucia Corno; Eliana La Ferrara (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Can providing information to potential migrants influence their decisions about risky and irregular migration? We conduct an experiment with over 7,000 secondary school students in Guinea, providing information through video testimonials by migrants who settled in Europe and through aggregate statistics. We implement three treatments: (i) information about the risks of the journey; (ii) information about economic outcomes in the destination country; and (iii) a combination of both. One month after the intervention, all treatments led students to update their beliefs about the risks and the economic outcomes of migration, resulting in decreased intentions to migrate. One year later, the Risk Treatment resulted in a 51% decline in migration outside Guinea. This effect was driven by a decrease in migration without a visa (i.e., potentially risky and irregular) and was more pronounced among poorer students. These findings are consistent with the predictions of a model where individuals choose between not migrating, migrating regularly, or migrating irregularly, and where information increases the perceived cost of irregular migration, thus decreasing migration among poorer students who cannot afford regular migration. Keywords:
Keywords: F22; O15; J61; D8; C93; 330; irregular migration; trafficking; information experiment; Guinea